2011
DOI: 10.1038/ismej.2011.133
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of epibiotic bacteria along the life cycle of the hydrothermal shrimp Rimicaris exoculata

Abstract: The caridean shrimp Rimicaris exoculata dominates the fauna at several Mid-Atlantic Ridge hydrothermal vent sites. This shrimp has an enlarged gill chamber, harboring a dense ectosymbiotic community of chemoautotrophic bacteria associated with mineral oxide deposits. Until now, their acquisition is not fully understood. At three hydrothermal vent sites, we analyzed the epibionts diversity at different moult stages and also in the first stages of the shrimp life (eggs, hatched eggs (with larvae) and juveniles).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
159
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(173 citation statements)
references
References 67 publications
12
159
2
Order By: Relevance
“…That the presence of an electron donor increases the carbon fixation rate indicates that Na 2 S 2 O 3 , and Fe 2 þ at least contribute to fuelling R. exoculata epibionts, and our autoradiography data suggest that chemosynthesis occurs at least in the large filamentous bacteria (epsilonproteobacteria of Marine Group 1), which appeared more intensely labelled than the thin filamentous and rod-shaped ones (epsilonproteobacteria of Marine Group 2 and gammaproteobacteria). The view that R. exoculata epibionts have sulphide-oxidising activity is consistent, moreover, with the fact epsilon-and gammaproteobacteria are assumed to have such activity, on the basis of the group affiliation of the former (Petersen et al, 2009;Goffredi, 2010;Guri et al, 2012) and because the latter possess functional SoxB and aprA genes (Hü gler et al, 2010(Hü gler et al, , 2011. We cannot say, however, what the epibiotic bacteria of R. exoculata use as predominant energy source.…”
Section: Carbon Fixation By Bacterial Chemosynthesismentioning
confidence: 76%
See 4 more Smart Citations
“…That the presence of an electron donor increases the carbon fixation rate indicates that Na 2 S 2 O 3 , and Fe 2 þ at least contribute to fuelling R. exoculata epibionts, and our autoradiography data suggest that chemosynthesis occurs at least in the large filamentous bacteria (epsilonproteobacteria of Marine Group 1), which appeared more intensely labelled than the thin filamentous and rod-shaped ones (epsilonproteobacteria of Marine Group 2 and gammaproteobacteria). The view that R. exoculata epibionts have sulphide-oxidising activity is consistent, moreover, with the fact epsilon-and gammaproteobacteria are assumed to have such activity, on the basis of the group affiliation of the former (Petersen et al, 2009;Goffredi, 2010;Guri et al, 2012) and because the latter possess functional SoxB and aprA genes (Hü gler et al, 2010(Hü gler et al, , 2011. We cannot say, however, what the epibiotic bacteria of R. exoculata use as predominant energy source.…”
Section: Carbon Fixation By Bacterial Chemosynthesismentioning
confidence: 76%
“…Authors have also identified gamma-proteobacterial epibionts of the Thiotrichaceae family (Leucothrix group), together with some free-living members and some other invertebrate ectosymbionts, mainly of crustaceans (Goffredi, 2010). These gammaproteobacteria appearing at least as filamentous and rod-shaped morphotypes can probably grow as sulphide oxidisers, most likely using the APS pathway for energy generation and the Calvin-Benson-Bassham cycle for carbon fixation (aprA and cbbM gene sequences, respectively) (Zbinden et al, 2008;Hü gler et al, 2010Hü gler et al, , 2011Guri et al, 2012). In addition, coccoidshaped cells with intracytoplasmic membrane stacks have been identified as type-I methanotrophic gammaproteobacteria (pmoA gene sequence) (Corbari et al, 2008a;Zbinden et al, 2008;Guri et al, 2012), and deltaproteobacteria related to Desulfocapsa have been identified thanks to their aprA and hydrogenase gene sequences (Hü gler et al, 2011), suggesting they can grow lithotrophically using hydrogen as electron donor for sulphate reduction.…”
Section: Carbon Fixation By Bacterial Chemosynthesismentioning
confidence: 99%
See 3 more Smart Citations